Pengaruh Penggunaan Simulasi Interaktif PhET terhadap Peningkatan Pemahaman dan Self-Efficacy Siswa pada Materi Grafik Fungsi - Sesilia Irmaya Bulu; Timotius Woda Napu; Yustina Bulu (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of using PhET simulation on students’ understanding of function graph concepts and their self-efficacy. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The subjects consisted of two groups: an experimental group using PhET simulation and a control group using conventional learning, each consisting of 13 students. The research instruments included a conceptual understanding test and a self-efficacy questionnaire administered before and after the learning process. Data were analyzed using descriptive and inferential statistics, including the Shapiro–Wilk test, Wilcoxon test, and Mann–Whitney test. The results showed that both groups experienced improvements in conceptual understanding and self-efficacy, with greater improvement observed in the experimental group. The Mann–Whitney test indicated a significant difference between the two groups in both conceptual understanding and self-efficacy (p < 0.05). Therefore, it can be concluded that the use of PhET simulation is effective in improving students’ understanding of function graph concepts and their self-efficacy.